Referrals to mental health services among adolescents in England by social strata: National cohort study - Lewis, Kate; Dale, Helen; Lewer, Dan; Blackburn, Ruth (International Journal of Population Data Science, 2025)
Objectives Rates of mental health difficulties and use of mental health services among adolescents have increased in the last decade. Understanding patterns of this service use is a vital step to ensuring equity in access. We described referrals to mental health services amongst secondary school pupils in England, by social strata. Method We used linked administrative educational-health records from Education and Child Health Insights from Linked Data (ECHILD). We created a national cohort of pupils in Year 7 of state-funded school (age 11 years at entry) from 2012/13 to 2021/22. Social strata, indicated by gender, racial-ethnic group, free school meal (FSM) eligibility, the index of multiple deprivation (IMD) and region of residence were measured at Year 7. Referrals to mental health services were captured by records in the mental health services dataset. Pupils were followed up until the first chronological event of: a referral, death or end of study (31st August 2022). Results Of 5,649,051 pupils,18.3% (1,033,186) had ≥1 referral to mental health services recorded during follow up, a rate of 47.9 per 1000 person-years (95% confidence interval 47.9-48.0). Females (57.5, 57.4-57.7) had higher rates than males (39.1, 39.0-39.2). White Irish Traveller (75.5, 70.7-80.5) and Mixed Black Caribbean and White (69.1, 68.2-70.0) pupils had the highest rates within racial-ethnic groups, whereas pupils from all Asian groups had the lowest rates (21.2, 21.0-21.3). Pupils with FSM eligibility (80.4, 80.1, 80.7) had double the rates compared to those not FSM eligible (41.9, 41.8, 42.0), and a socioeconomic gradient was present by IMD group. Within region of residence, rates were highest in the North-East (61.9, CI 61.5, 62.4) and lowest in London (39.5, 39.3, 39.7). Conclusion We present the first national estimates of referrals to mental health services within a school cohort. Almost one fifth of pupils were referred, with stark variation by social strata. Next, we will explore mental health-related contacts across multiple health services to further explore inequities in access.